Linker Nups connect the nuclear pore complex inner ring with the outer ring and transport channel - Fischer, Jessica; Teimer, Roman; Kunze, Ruth; Hurt, Ed (Nature structural & molecular biology, 2015)
Nuclear pore complexes (NPCs) mediate transport between the nucleus and cytoplasm. NPCs are composed of ∼30 nucleoporins (Nups), most of which are organized in stable subcomplexes. How these modules are interconnected within the large NPC framework has been unknown. Here we show a mechanism of how supercomplexes can form between NPC modules. The Nup192 inner-pore-ring complex serves as a seed to which the Nup82 outer-ring complex and Nsp1 channel complex are tethered. The linkage between these subcomplexes is generated by short sequences within linker Nups. The conserved Nup145N is the most versatile connector of NPC modules because it has three discrete binding sites for Nup192, Nup170 and Nup82. We assembled a large part of a Chaetomium thermophilum NPC protomer in vitro, providing a step forward toward the reconstitution of the entire NPC.
Gesehen am 03.08.2021